The Effect of Health Education About Tuberculosis on Knowledge and Attitudes Toward Preventing the Transmission of Tuberculosis in the Families of TB Patients at the Purbalingga Community Health Center - Shinta Dewi Dian Puspitasari; Maya Safitri; Tin Utami (International Journal Of Health Science, 2026)
Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis and transmitted through the air when individuals with pulmonary TB cough and release bacteria that can be inhaled by others. Preventive efforts are necessary to reduce its spread, and health education is one strategy to increase public awareness. This study aimed to examine the effect of tuberculosis health education on the knowledge and attitudes of families in preventing TB transmission among patients’ families at the Purbalingga Community Health Center. This quantitative study used a pre-experimental method with a one-group pre-test–post-test design. A total of 48 families of TB patients were selected using purposive sampling. Data were collected through questionnaires measuring respondents’ knowledge and attitudes. Most respondents were female (79.2%), aged 46–55 years (39.6%), related to the patient as siblings (37.5%), and had a senior high school or vocational school education level (56.3%). The findings showed that knowledge improved from the adequate category before education (64.6%) to the good category after education (72.9%). Attitudes also changed significantly from mostly negative (66.7%) to positive (95.8%) after the intervention. Statistical analysis using the Paired Sample T-Test showed a p-value of 0.000 (<0.05), indicating a significant effect of health education on improving knowledge and attitudes toward preventing TB transmission. These results indicate that health education is an effective intervention to increase awareness and promote preventive behavior among families of TB patients.